CAPABILITY LEARNING ON SPEAKING IN ARABIC (An Ethnographic Study at Arabic Department Of FITK UIN Syarifhidayatullah Jakarta) - Akmal Walad Ahkas; Zainal Rafli; Aceng Rahmat (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2017)
This study aimed to obtain an extensive understanding regarding to learning ability on to speak in Arabic at Department of Arabic Education Faculty of Tarbiyah and Teacher Training UIN SyarifHidayatullah Jakarta. This study involves qualitative method comprehending ethnographic method by Spradley model. This study lasted from November 2015 to June 2016. The data was obtained from participatory observation, interview, documentary analysis, and audio-visual material. This study proves that: (1). the learning objective is considered by the level of Muhâdatsahthat is divided into level 1, level 2, and level 3. (2). Curriculum applies on KKNI basis (National Education Quality Standard).  And the syllabus applies Functional Syllabus. (3).  Scenario of the learning material covers themes on conversation, vocabulary, the maqala concerning to the most recent development and attractive topic on argumentative debate relating to educational issues. (4). The method involves Eclectic Method that organises Grammar-Translation method, Direct Method, Audio-Lingual Method, and Debating Method. (5). The media of learning is equipped by powerpoint presentation, video (native speaker), and printed materials. (6) the evaluation is conducted on the performance basis to assess the ability on Arabic through communicative activity, orally and in writing. (7) the lingual environment is supported by formal and informal environment.